1985
DOI: 10.1111/j.1476-5381.1985.tb10554.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopexamine: a novel agonist at peripheral dopamine receptors and β2‐adrenoceptors

Abstract: 1 Dopexamine is an agonist at peripheral dopamine receptors and at P2-adrenoceptors.2 Dopexamine has approximately one-third the potency of dopamine in stimulating the vascular DA,-receptor in the dog, resulting in a fall in renal vascular resistance of 20% at 2.3 x 10-8 mol kg-' (i.a.). 3 Prejunctional DA2-receptors are also stimulated by dopexamine, resulting in a reduction of neurogenic vasoconstriction in the rabbit isolated ear artery (IC5o of 1.15 x 10-6 M) and of neurogenic tachycardia in the cat (ID5o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
3

Year Published

1985
1985
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(57 citation statements)
references
References 26 publications
1
53
0
3
Order By: Relevance
“…Equally, lack of desensitization of atrial PI-receptors following 7-day dopexamine infusion was not a surprising result since dopexamine has been reported to be only a weak agonist at the 3,-receptors of the guinea-pig right atria (Mitchell et al, 1987), with an intrinsic activity of only 0.1 relative to isoprenaline (Brown et al, 1985). In the guinea-pig left atria, it was found to have no intrinsic activity and therefore to act as a P1-receptor antagonist (Williams et al, 1990).…”
Section: -Adrenoceptor-mediated Atrial Responsesmentioning
confidence: 96%
See 1 more Smart Citation
“…Equally, lack of desensitization of atrial PI-receptors following 7-day dopexamine infusion was not a surprising result since dopexamine has been reported to be only a weak agonist at the 3,-receptors of the guinea-pig right atria (Mitchell et al, 1987), with an intrinsic activity of only 0.1 relative to isoprenaline (Brown et al, 1985). In the guinea-pig left atria, it was found to have no intrinsic activity and therefore to act as a P1-receptor antagonist (Williams et al, 1990).…”
Section: -Adrenoceptor-mediated Atrial Responsesmentioning
confidence: 96%
“…The potency of isoprenaline in the pulmonary artery was approximately 10 fold less than its potency in the left atria and 8 fold less than its potency in right atria. Although the dose of dopexamine was higher (240 pg kg-' h-'), it has been shown that dopexamine is considerably less potent than isoprenaline in producing 12-receptor-mediated relaxation of the guinea-pig uterus, where its intrinsic activity is also less than that of isoprenaline (a = 0.78) (Williams et al, 1990), although it acts as a full agonist in guinea-pig trachea (Brown et al, 1985). Therefore, it is conceivable that the dose of dopexamine may also have been insufficient to induce desensitization of pulmonary arterial P2-receptors, especially if dopexamine acts as a partial agonist in that tissue; partial agonists have been shown to be less effective in producing P-receptor desensitization than full agonists (Pittman et al, 1984;Neve et al, 1985).…”
Section: P2-adrenoceptor-mediated Vascular Responsesmentioning
confidence: 99%
“…In animal studies, intravenous dopexamine administration is followed by a moderate fall in blood pressure, an increase in heart rate and left ventricular peak dP/dt.P'-, and renal and mesenteric vasodilation (Brown et al, 1984b(Brown et al, , 1985a.…”
Section: Introductionmentioning
confidence: 99%
“…The cardiovascular effects ofdopexamine were examined and compared with dopamine in pentobarbitone-anaesthetized and in conscious dogs. A preliminary account of this work was presented to the British Pharmacological Society (Brown et al, 1984).…”
Section: Introductionmentioning
confidence: 99%